MINAT MAHASISWA AKUNTANSI UNTRIM SEBAGAI PENGGUNA E-WALLET DENGAN MEMPERTIMBANGKAN PERSEPSI KEMANFAATAN, PERSEPSI KEMUDAHAN, DAN PERSEPSI KEPERCAYAAN - Salepa Celik Misrami Afolo; Ni Nyoman Sri Rahayu Trisna Dewi (KRISNA: Kumpulan Riset Akuntansi, 2022)
This study aims to determine the effect of Perception of Benefits (X1), Perception of Ease (X2), Perception of Trust (X3), Interest of E-wallet Users on the interest of Untrim Accounting Students as E-Wallet users (Y). This research uses quantitative research methods with associative research types. The population in this study were students of the Accounting Study Program at Triatma Mulya University batch 2017, 2018, and 2019. The sample was taken using the purposive sampling method with a sample of 74 respondents. During the Covid-19 pandemic, which is in accordance with government policy, that learning activities are carried out online, the data collection in this study used an online questionnaire via google form and the measurement used a Likert scale. And the data analysis methods used are Data Quality Test, Classical Assumption Test, Multiple Regression Analysis, F Test (Model Feasibility), and t Test. The results obtained from the data analysis showed that the perception of benefits, the perception of ease, and the perception of trust partially had a positive and significant effect on the interest of E-Wallet users.